Cruelty against animal: looking at the law / Mazyu Syaziana Mohd Yusof and Mira Mirna Musa. - Mohd Yusof, Mazyu Syaziana; Musa, Mira Mirna (2007)
Basically, our research is about animal cruelty and the law that governs it in Malaysia. Our aim in doing this research is to fill in the loop hole in our local legislation which we think is not sufficient to protect the animal rights in Malaysia. What this project set up to do is to amend the current law to make it more severe in punishing the abuser. Besides that, we also discuss on how to educate the public regarding animal cruelty. By doing this research, we realize that there actually exist errors in the current legislation. That is why we are proposing for a higher penalty to be imposed so that animal cruelty cases will decrease. As a conclusion, we got to know that this research will not only gives benefit to the helpless animals but also to people who fight for animal rights. Furthermore, it is time for our legislator to make certain amendment to the existing legislation in order to move one step further.